Design, fabrication and testing of a coated conductor magnet for electrodynamic suspension. (31st December 2021) - Ma, Guangtong; Gong, Tianyong; Wang, Ruichen; Li, Songlin; Nie, Xingchao; Zhou, Pengbo; Li, Jing; Li, Chao; Ge, Zhengfu; Cui, Hengbin
Abstract: The coated conductor magnet, as the onboard magnet of the electrodynamic suspension (EDS) train, is deemed promising due to its relatively high operating temperature, low cooling cost, and good mechanical tolerance, making the liquid-helium-free high-temperature superconducting (HTS) EDS train possible. In order to promote the progress of the HTS EDS train, this work aims at designing, fabricating and testing a coated conductor magnet as the onboard magnet of EDS train. The HTS magnet is designed with the comprehensive considerations of the electromagnetic calculation, thermal–mechanical coupling analysis, as well as the heat load estimation. The magnet is conduction-cooled without any coolant. A radiation shield was used to reduce the heat leakage, enabling the cryogenic system to provide a better low-temperature environment for the magnet. Through a deliberate design, the magnet was fabricated, including two HTS coils and the tailored cryogenic system. Afterwards, the electromagnetic and thermal performances of this magnet were tested and analysed in detail. It was proven that the magnet can be cooled to below 15 K; besides, the magnet has been successfully charged to 240 A. Further increase in the current is possible because of the high safe margin of the critical currents for both the HTS magnet and its current lead, although a slight performance degradation was observed on two double-pancake coils inside the magnet. The present study will provide useful implications for the design and application of onboard HTS magnets in EDS train.